Production performance and blood biochemical changes in broiler chickens fed amla during induced-stress conditions - NAKAJOTHI, N; NANJAPPAN, K; SELVARAJ, P; JAYACHANDRAN, S; VISHA, P (The Indian Journal of Animal Sciences, 2011)
An experiment was conducted in broiler chickens to evaluate the efficacy of Emblica officinalis (amla) fruits rich in vitamin C in alleviating stress induced by ACTH injection @ 3 IU / kg body weight for 5 d from 22 d of age. The birds were fed standard broiler diet supplemented with 5, 10 or 20 g amla dry powder or 250 mg synthetic vitamin C / kg diet. Body weight and feed efficiency were measured weekly. The plasma glucose, serum total cholesterol, high-density lipoprotein and triglycerides were measured at 21, 28 and 42 d of age. The results suggested that while the mean body weight was not influenced by amla supplementation, the feed efficiency was significantly improved by 10 g / kg amla feeding, compared to other groups. Serum triglycerides level decreased in amla-fed groups compared to control at third and fourth weeks of age. Other blood biochemical parameters like plasma glucose, serum total cholesterol and highdensity lipoprotein did not vary between treatments. It can be concluded that the broiler diet can be supplemented with amla at 10 g / kg as an anti-stress agent during stress periods of broiler production.Â